2010
DOI: 10.3171/2009.8.jns08731
|View full text |Cite
|
Sign up to set email alerts
|

True posterior communicating artery aneurysms: are they more prone to rupture? A biomorphometric analysis

Abstract: These data suggest that true PCoA aneurysms have a larger PCoA relative to the ipsilateral P(1) segment. To the authors' knowledge, this represents the first such biomorphometric comparison of these different types of PCoA aneurysms. Although statistically smaller in size, true PCoA aneurysms also have a similar prevalence of presenting as a ruptured aneurysm, suggesting that they might be more prone to rupture than a junctional aneurysms of similar size. Further analysis will be required to determine the biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 35 publications
4
33
0
Order By: Relevance
“…However, follow-up studies have found that the majority of PCoA aneurysms rupture at smaller sizes than would be expected based on ISUIA [6], [14], [23]. This may represent the fact that flow induced hemodynamic stress involved at aneurysm site is important for rupture, independent of the size of the aneurysm itself [24][28].…”
Section: Discussionmentioning
confidence: 97%
“…However, follow-up studies have found that the majority of PCoA aneurysms rupture at smaller sizes than would be expected based on ISUIA [6], [14], [23]. This may represent the fact that flow induced hemodynamic stress involved at aneurysm site is important for rupture, independent of the size of the aneurysm itself [24][28].…”
Section: Discussionmentioning
confidence: 97%
“…Because fetal PCOM arteries are the only supply to the PCA, care must be taken not to compromise flow to this artery during clipping or coiling of PCOM artery aneurysms [8]. The aneurysm neck originates from the PCOM artery in 0.1–2.8% of all aneurysms and 4.6–13% of PCOM artery aneurysms [8, 9]. These aneurysms are encountered mostly with large or fetal PCOM arteries and pose a challenge to coiling and clipping due to the carefulness required to maintain the flow through the PCOM [9].…”
Section: Discussionmentioning
confidence: 99%
“…The aneurysm neck originates from the PCOM artery in 0.1–2.8% of all aneurysms and 4.6–13% of PCOM artery aneurysms [8, 9]. These aneurysms are encountered mostly with large or fetal PCOM arteries and pose a challenge to coiling and clipping due to the carefulness required to maintain the flow through the PCOM [9]. With fetal PCA, it is necessary to have an optimal dome to neck ratio for safe coiling.…”
Section: Discussionmentioning
confidence: 99%
“…11,15 A recent study on the natural course of unruptured cerebral aneurysms conducted in a Japanese cohort (Unruptured Cerebral Aneurysm Study [UCAS]) showed that a PCoA aneurysm is more likely to rupture. 28 Thus, knowledge of risk factors for rupture is thought to be crucial for managing patients with PCoA aneurysms.…”
Section: Discussionmentioning
confidence: 99%